Reproducibility of double agar gel immunodiffusion test using stored serum and plasma from paracoccidioidomycosis patients - Tomazini, Karina Andressa [UNESP]; Pereira, Beatriz Aparecida Soares [UNESP]; Sylvestre, Tatiane Fernanda; de Souza Cavalcante, Ricardo [UNESP]; de Carvalho, Lídia Raquel [UNESP]; Mendes, Rinaldo Poncio [UNESP] (FapUNIFESP (SciELO), 2023)
Background: Serological evaluation performed by double agar gel immunodiffusion test (DID) is used for diagnosis, evaluation of severity, management of paracoccidioidomycosis patients, and development of new clinical studies. For these reasons, the Botucatu Medical School of UNESP maintains a serum bank at the Experimental Research Unit with patient clinical data. This study aimed to evaluate the influence of the freeze-thaw cycle and different blood matrices on the titration of circulating antibodies. Methods: The study included 207 patients with confirmed (etiology-demonstrated) or probable (serology-demonstrated) paracoccidioidomycosis, and DID was performed with culture filtrate from Paracoccidioides brasiliensis B339 as antigen. First experiment: the antibody levels were determined in serum samples from 160 patients with the chronic form and 20 with the acute/subacute form, stored at –80oC for more than six months. Second experiment: titers of 81 samples of serum and plasma with ethylenediaminetetraacetic acid (EDTA) or heparin, from 27 patients, were compared according to matrix and effect of storage at –20oC for up to six months. Differences of titers higher than one dilution were considered discordant. Results: First experiment: test and retest presented concordant results in serum stored for up to three years, and discordant titers in low incidence in storage for four to six years but high incidence when stored for more than six years, including conversion from reagent test to non-reagent retest. Second experiment: serum, plasma-EDTA and plasma-heparin samples showed concordant titers, presenting direct correlation, with no interference of storage for up to six months. Conclusions: Storage at –80oC for up to six years has no or little influence on the serum titers determined by DID, permitting its safe use in studies depending on this parameter. The concordant titrations in different blood matrices demonstrated that the plasma can be used for immunodiffusion test in paracoccidioidomycosis, with stability for at least six months after storage at –20oC.
Keywords: Blood matrices; Paracoccidioidomycosis; Plasma; Serological diagnosis; Serum; Storage